Pediatric Trainee Perspectives on the Decision to Disclose Medical Errors. Issue 2 (8th March 2022) - Lin, Matthew; Horwitz, Leora; Gross, Rachel S.; Famiglietti, Hannah; Caplan, Arthur
Abstract : Supplemental digital content is available in the text. Abstract : Purpose: The aim of the study was to describe factors that may impact pediatric trainees' willingness to disclose medical errors using clinical vignettes. Methods: A single-center cross-sectional anonymous survey of pediatric residents and fellows at a large urban medical center in 2019 was conducted. Trainees were provided with clinical vignettes depicting an error resulting in a serious safety event (SSE), minor safety event (MSE), and near miss safety event (NMSE) and were asked to classify the type of safety event and rate and explain their agreement or disagreement with disclosure. Survey items also evaluated trainees' personal experiences with errors and disclosure. Descriptive and correlational analyses were used to characterize responses. Qualitative content from open-ended survey questions was analyzed using the constant comparative method. Results: Of 126 trainees, 42 (33%) completed the survey. All agreed with disclosing the hypothetical error presented in the vignette resulting in an SSE (100%), with rates falling for the MSE (95%) and NMSE (7%). There were no significant associations between disclosure agreement for the vignettes and trainee demographic features, knowledge of safety events, prior personal experiences with errors, and disclosure. Four themes that emerged from qualitative analysis of trainees' rationales for disclosure or nondisclosure of the vignette errors are harm, parental preferences, ethical principles, and anticipatory guidance. Conclusions: Trainees had high rates of disclosure for the vignette errors cases that depicted SSEs and MSEs but lower rates for NMSEs. Trainees considered the type and level of harm caused, parental preferences, upholding ethical principles, and the need for anticipatory guidance in their rationales for disclosure or nondisclosure of the vignette errors.